The Role of Public Health Partnerships in the Success of the Jackson Heart Study Undergraduate Training and Education Center - White, Wendy B. (Ethn Dis, 2020)
BACKGROUND: The Jackson Heart Study (JHS) is a single-site prospective epidemiologic investigation of cardiovascular disease (CVD) among African Americans from the central Jackson, Mississippi area. The study is a collaboration between Jackson State University (JSU), University of Mississippi Medical Center (UMMC), Tougaloo College (TC), and the Mississippi State Department of Health (MSDH). The JHS Undergraduate Training and Education Center (JHSUTEC) at TC was developed to increase the numbers of college-aged African American students entering public health and health-related fields. To achieve this goal, the UTEC designed the Jackson Heart Study (JHS) Scholars program. METHODS: JHS Scholars are required to take additional classes and participate in public health and/or biomedical research. The scholars engage in research locally during the academic year. However, many scholars participate in research outside of the Jackson Metropolitan area during the summer. Because of this, national collaborators were needed to act as mentors and hosts. RESULTS: Since the inception of the JHSUTEC, more than 15 collaborations have been formed that have shared resources and student successes. As of May 2018, more than150 students have successfully completed the JHS Scholars program and many have continued into careers in public health, biomedical research, and medicine. Since 2004, JHS scholars have published 29 papers and 15 scholars have received diversity supplements. CONCLUSION: Collaborative activities and public health partnerships have contributed to the success of the JHSUTEC program and have served as a pathway of entry into STEM fields for minority students.